Novel Digital Gait Kinematic Solution to Improve Frailty - Rodgers, Geraldine; Mottley, Anne; Hodgins, Diana (British Journal of Healthcare and Medical Research, 2020)
Introduction: Frailty effects a person’s health and correlates with mobility and falls. Intervention studies that focus on exercise have demonstrated improved mobility and functional ability in some frailty groups. This study tested a personalised intervention programme automatically generated from digital gait data on frail older people under the care of the North East London Foundation Trust, Community Hospital setting. Methods: One hundred and twenty one people, average age 79, who suffered an injurious fall and were under the care of the Community Hospital, completed the personalised intervention programme. Objective gait kinematic data, obtained using GaitSmartTM automatically generated a personalised exercise programme. Each participant received four tests, approximately 3 weeks apart and was provided with a copy of their report plus personalised exercises. Frailty was measured using the Edmonton Frailty Scale (EFS), fear of falling was measured using the Falls Efficacy Scale-International (FES-I) and speed was determined from the gait data (GS). Results: Five parameters were analysed for all 121 participants at the start and end of the intervention: EFS; FES-I; GS; speed; walking aid. There was a statistically significance between the start and end (p<0.001) for all the parameters. Conclusion: The results demonstrate that addressing frailty using a digital gait solution that sets exercises based on the gait kinematic data, did reverse frailty. This four session programme has shown to improve frailty levels and fear of falling. It also reduced the reliance on walking aids and increased average walking speed from 0.46 to 0.62 m/s.